Entrepreneurial Management Practices of School Principals to Enhance Financing Standard Quality in Primary Education - Feranida Feranida; Saiful Bahri; Cut Khairani (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2025)
This study examines the implementation of entrepreneurial management by primary school principals in addressing the limitations of School Operational Assistance (BOS) funding in Bireuen District, Aceh, Indonesia. Using a qualitative multiple case study design, the research explores how two public primary schools—SDN 8 Peusangan and SDN 18 Peusangan—develop and sustain entrepreneurship-based financial models under resource constraints. Data were collected through semi-structured interviews, observations, and document analysis, and analyzed thematically with the aid of NVivo 12 software. The findings reveal that transformational leadership plays a central role in mobilizing internal resources, stimulating innovation, and fostering collective participation in entrepreneurial initiatives. Entrepreneurial programs such as canteens, herbal gardens, and school bazaars generated an average of 5.3% additional income relative to BOS funds and contributed to improving educational quality and financial transparency. Through the lens of the Resource-Based View (RBV), effectuation theory, and stakeholder theory, the study identifies dynamic capabilities in sensing and seizing opportunities, as well as building multi-level stakeholder collaboration for sustainable school financing.This research extends the literature by developing an integrative “Transformative-Effectual Model” that links transformational leadership with entrepreneurial management and dynamic capabilities within the context of basic education. Unlike prior studies that focus on higher education entrepreneurship, this study empirically demonstrates how elementary schools can transform limited resources into value-creating ventures, offering a replicable framework for education systems in developing regions. The results have implications for policy on hybrid school financing, leadership development, and innovation in public education governance.